Building Online Marketing and Digital Branding in The Middle of The COVID-19 Pandemic - Hongky Dyrgo (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the impacts of the COVID-19 pandemic is the decline in business and the economy. Thus, marketers and entrepreneurs must find alternative solutions to market their products or services to consumers. Optimizing business people's online marketing and digital branding as a means of communication with their target consumers Matter This is certainly a very effective choice during this pandemic. Research objectives in articles here are two. 1) analyze online marketing and digital branding. 2) Describe marketing online and digital branding in the midst of the COVID-19 pandemic. This type of research is based on research references whose data retrieval is oriented toward several appropriate references. Focus This research is to build online marketing and digital branding in the midst of the COVID-19 pandemic. 19. The validity of the data in this article is based on various sources and an extended period of time. The data analysis technique used in this article is the constant comparison method. The results of the research in this article are twofold. 1) Online and digital marketing analysis and branding 2) Describe online marketing and digital branding in the midst of the COVID-19 pandemic.